Issues and Challenges of English Teachers - Lakshmi Subramanian (International Journal of Engineering and Management Research, 2022)
There have been many instances in which English has been referred to as the "global language" because it is used in many countries worldwide. As a major resource for the modern world, English is not only the universal language of the current era but it is the dominant language in every country in the world [1]. Considering the great ethnic and linguistic diversity of the nation, English is used not only for communication purposes but also for coordination purposes between states and within states as the country is characterized by a large ethnic and linguistic diversity. Although modern technology has played an important role in teaching and learning the language in schools and colleges in particular in small towns, it is inadequate and unproductive in the case of small towns and rural areas [2]. During the course of becoming an effective teacher, teachers are encouraged to practice a “reflective mind” so that they can gain insight into what is happening in the classroom and learn what works and doesn't work [1][3]. The global economy and the competitive market of English education will present many challenges for teachers, especially English language teachers, primarily because of the competitive nature of English education as a profession, but also because of the demanding nature of a teaching career [2]. The purpose of this study was to identify the issues and challenges encountered by fifteen teacher-trainees during their teaching practicum, as well as to examine the factors that assisted in the identification of those issues and challenges. It was identified that narrative inquiry was the best method to identify challenges and issues experienced in their teaching practice. It was found that students struggle with listening to and understanding English. The reason for this is unclear. How can these problems be alleviated? We are discussing the influence of rural pockets of India on second language acquisition, as well as the factors that slow its acquisition. These problems can be rectified successfully through appropriate and adequate remedial measures.